Free agency and its place within psychology. - Pitman, Michael M. (My University, 2011)
Philosophical tradition locates questions about free will and agency within a debate characterised by deep cognitive tensions and a lingering sense of stalemate. Evaluating the most promising libertarian account of free will, due to Robert Kane, confirms the compatibilist worry that inserting indeterminism into moments of volition undermines claims of agency; while testing the prospects for compatibilism in a deterministic universe confirms the libertarian suspicion that free agency is not compatible with global determinism. An alternative setting for the exploration and defence of free agency is proposed, located closer to Psychology, and framed by the images of the Agent Automaton (AA) and the Hyperrational, Hyper-reflective Agent (HHA). Giving psychological substance to the threat of the AA helps provoke fresh explorations and defences of a distinctively human, conscious free agency; while the evidence against, and questions about the normative desirability of our being HHAs argue against securing claims of free agency by making empirically and normatively unreasonable demands on our capacities for reflection, cool reason, and control. The project of explicating and defending a psychologically-informed conception of free agency, exploiting degrees of freedom in our imagination and externalised aspects of mind, is given positive substance and direction, including a speculative hypothesis for locating a freedom-friendly variety of indeterminism in processes of imaginative generativity.